Developmenl of creative features in students artly-graphic faculty - N.V. Shilavtseva; S.V. Inozemtseva; N.V. Chen (Academy of Cognitive and Natural Sciences, 2006)
The article и devoted to artistic development of students. especially to forming of its artistic outlook. Special attention is paid to abilities of art as the basis offorming of artistic outlook of students.